1993
DOI: 10.3354/dao016001
|View full text |Cite
|
Sign up to set email alerts
|

Light and electron microscopic comparisons of normal hepatocytes and neoplastec hepatocyles of well-differenciated hepatocellular carcinomas in a teleost fish

Abstract: ABSTRACT. Well-differentiated hepatocellular carcinomas (HCC's) induced in the sheepshead minnow Cyprinodon variegatus w~t h N-nitrosodiethylamine perm~tted light microscop~cal and ultrastructural comparisons of normal hepatocytes and adjacent HCC cells. Normal hepatocytes contained typical organelles with their intracellular distribution similar to that described for other teleosts. These cells revealed a strong compartmentalization of organelles consisting of restricted perinuclear cytoplasm containing rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
1
1
0
1
Order By: Relevance
“…Furthermore, electron microscopy confirmed the histopathological changes and showed the presence of HCC in the DENA-treated group, as indicated by mitochondrial accumulation, RER stacks and nuclear malignant changes. These results were consistent with a previous study, which demonstrated that normal hepatocytes had fewer mitochondria as compared with HCC cells (66). In addition, HCC cells were shown to contain a greater abundance of, and more widely dispersed, RER.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, electron microscopy confirmed the histopathological changes and showed the presence of HCC in the DENA-treated group, as indicated by mitochondrial accumulation, RER stacks and nuclear malignant changes. These results were consistent with a previous study, which demonstrated that normal hepatocytes had fewer mitochondria as compared with HCC cells (66). In addition, HCC cells were shown to contain a greater abundance of, and more widely dispersed, RER.…”
Section: Discussionsupporting
confidence: 94%
“…In teleost livers, a large number of morphological studies of the hepatic cells, hepatocytes (Langer, 1979;Nopanitaya et al ., 1979b), endothelial cells (Ferri and Sesso, 1981;Sato and Yamamoto, 1983), hepatic stellate cells (Nopanitaya et al ., 1979b;Eastman and De Vries, 1981), Kupffer cells (Hampton et al ., 1987;Rocha et al ., 1997) and bile ductules cells (Shin, 1978;Tanuma, 1980;Satoh, 1983), in the hepatic lobule, and the biliary system (Hampton et al ., 1985; and innervation (Esteban et al ., 1998), have revealed details of their connection (Sakano and Fujita, 1982;Hampton et al ., 1989;Speilberg et al ., 1994), and established the liver structures and functions (Motta, 1984). The recent aims have been as follows: (1) ecological and toxicological studies of the liver as a biomarker of environmental pollution (Braunbeck, 1994), (2) a histochemical study to establish whether the liver has a central role in metabolism (Orbea et al ., 1999;Jung et al ., 2002), (3) a pathological study of the liver as an important organ for the analysis of fish diseases (e.g., cholestasis and neoplasm) (Couch, 1991;1993;Okihiro and Hinton, 2000). From current zoological viewpoints, the themes of biodiversity or evolution have been focused and investigated (Gemballa et al ., 2003), but there has been little phylogenic research (Satoh, 1983;Cornelius, 1985;Akiyoshi et al ., 2001) in any vertebrates into the evolution of the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Tako je, i u izvedenom eksperimentu sa razliĉitim nivoima masti nabubrelost hepatocita, verovatno posledica intenzivne ishrane i procentualnog uĉešća masti u hrani. Vakuolizacija hepatocita se dogaĊa zbog morfoloških promena u citoplazmi i kompartmentacije preraspodele organela i vakuola u citoplazmi, usled ĉega se organele uglavnom nalaze u uskom krugu oko jedra, a u vakuolama koje nastaju se gomilaju rezervne materije, glikogen i/ili lipidi (Couch, 1993). Nalaz koji ukazuje na ekscentriĉnost jedara usled velikih vakuola, podudara se sa Caballero et al (1999) koji sliĉna ekscentriĉna jedra nalaze u ispitivanju jetre Sparus aurata zavisno od nivoa lipida i kvaliteta ribljeg brašna.…”
Section: Histološka Analize Unutrašnjih Organaunclassified